Are Filial Piety and Ethnic Community Engagement Associated With Psychological Wellbeing Among Older Chinese American Immigrants? A Cultural Resource Perspective. (February 2021) - Kim, Jeung Hyun; Silverstein, Merril
This research examined whether perceived receipt of filial piety from adult children and ethnic community engagement—two major ethnocultural resources—were associated with psychological wellbeing of older Chinese American immigrants. Analyses used data from the PINE study, a sample of older Chinese adults in Chicago. Tobit regression revealed that elders who received more filial piety and visited community centers experienced less loneliness and depression than their counterparts did. Tests of interactions showed that community center visits moderated the negative relationship between perceived filial piety and depression. Results suggest the importance of community engagement for diminishing depressive symptoms in older Chinese American immigrants, particularly those with culturally weak intergenerational ties. Discussion centers on how visiting community centers in ethnically dense neighborhoods compensates for unfulfilled filial piety expectations by protecting the mental health of minority elders within a rapidly growing and acculturating immigrant population.